INTEGRASI PETA KONSEP DENGAN PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI KELAS X SMA MUHAMMADIYAH 1 PEKANBARU TAHUN AJARAN 2017/2018 - Hidayati, Ira; Wulandari, Sri; Arnentis, Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to improve the learning outcomes of Biology in the cognitive domain of class X Muhammadiyah 1 Pekanbaru High School through Integration of Concept Maps with the Application of Problem Based Learning (PBL) Models. Biology learning outcomes in the cognitive domain are seen from the absorption and completeness of learning. The research procedure was carried out by the Classroom Action Research (CAR). The subjects of this study were students of class X MIA 3 of Muhammadiyah 1 High School in Pekanbaru 2017/2018 academic year, totaling 32 students, consisting of 13 men and 19 women. The results of this study indicate that the absorption of students increased from cycle I to cycle II from 81.00 (good category) to 83.96 (good category). Student completeness increased from cycle I to cycle II, with completeness percentage of 76.25% (sufficient category) to 81.25% (good category). From the results of this study it can be concluded that the Integration of Concept Maps with the Application of the Problem Based Learning Model (PBL) can improve Biology learning outcomes in the cognitive domain of class X of Muhammadiyah 1 Senior High School Pekanbaru.Key Words: Cognitive learning outcomes, Concept Maps, Integration, and Problem Based Learning.